The foxes that ruin the vineyards - a literal interpretation of Song of Songs 2:15 - Fischer, S. (Faculty of Theology, University of the Free State, 2003)
This article focuses on a literal interpretation of Song of Songs 2:15. Initially, this verse is identified as an independent unit, as a song intended to scare off. Now it forms part of a garden/countryside scenery (2:8-17). In 2:15 the co-workers of the lover are addressed. They are asked to create an intimate mood by setting the lover free from his work, and to catch the foxes instead of him.
Keywords: Exegesis: Old Testament; Song of Songs 2:15; Literal interpretation